Frequent mutations of chromatin remodeling genes in transitional cell carcinoma of the bladder - Gui, Yaoting; Guo, Guangwu; Huang, Yi; Hu, Xueda; Tang, Aifa; Gao, Shengjie; Wu, Renhua; Chen, Chao; Li, Xianxin; Zhou, Liang; He, Minghui; Li, Zesong; et al. (Nature genetics, 2011)
Zhiming Cai and colleagues report the exome sequencing of tumor and matched normal tissue from nine transitional cell carcinomas (TCCs) of the bladder, with further screening in 88 additional subjects. The authors identify mutations in chromatin remodeling genes in 59% of the 97 TCC subjects. Transitional cell carcinoma (TCC) is the most common type of bladder cancer. Here we sequenced the exomes of nine individuals with TCC and screened all the somatically mutated genes in a prevalence set of 88 additional individuals with TCC with different tumor stages and grades. In our study, we discovered a variety of genes previously unknown to be mutated in TCC. Notably, we identified genetic aberrations of the chromatin remodeling genes ( UTX, MLL - MLL3 , CREBBP - EP300 , NCOR1 , ARID1A and CHD6 ) in 59% of our 97 subjects with TCC. Of these genes, we showed UTX to be altered substantially more frequently in tumors of low stages and grades, highlighting its potential role in the classification and diagnosis of bladder cancer. Our results provide an overview of the genetic basis of TCC and suggest that aberration of chromatin regulation might be a hallmark of bladder cancer.